An economic analysis of exploration and extraction of oil on the UK continental shelf - Pesaran, M (Oxford Institute for Energy Studies, 1989)
This paper develops an econometric framework for the analysis of exploration and production policies of "price-taking" suppliers, and derives theoretically-consistent exploration and output equations for oil which explicitly take account of the oil discovery process and the intertemporal nature of exploration and production decisions. The framework is then applied to an empirical analysis of oil exploration and extraction on the United Kingdom Continental Shelf (UKCS). The analysis differs from the other econometric studies in the field in a number of respects: the output and exploration equations estimated in the paper are theory-consistent in the sense that they are both derived as solutions to a single - optimization problem. formation and presents formal tests of the hypothesis that oil price The paper pays careful attention to the problem of expectations expectations are formed rationally against the alternatives that they are formed adaptively or recursively. The empirical analysis also explicitly takes account of the available engineering information concerning the pressure dynamics of the petroleum reserves and the geological knowledge pertinent to the discovery process, and presents formal statistical tests of the significance of these factors for the explanation of output and investment policies of oil companies operating on the UKCS.